Trends in Knowledge Management within Open Government - Artha Rachma Widiastuti; Imam Yuadi (Forum Ilmu Sosial, 2023)
In realizing the aspirations as a democratic nation, the provision of high-quality information transparency by the government is essential, especially for the legislative body as the people's representation. To transform information into a fundamental consideration for public policies, effective knowledge management is needed from the community, who act as active users of this information transparency. This study aims to analyze the trends in research concerning knowledge management and open government. Data sources were obtained through the Web of Science for publications from 2019 to 2023, focusing on the fields of political science, management, and social reform. The applied method utilized bibliometric analysis with tools such as VOSviewer and Biblioshiny. The study's results identified a total of 2251 keywords, which were then refined to 259 keywords through data selection. From the VOSviewer analysis, the study yielded 1144 links and 4 clusters, indicating the interconnectedness among keywords. This interconnectedness was further illustrated through Network Visualization, Overlay Visualization, and Density Visualization. Meanwhile, the Biblioshiny analysis, conducted using the R Application, involved visualizations like WordCloud, TreeMap, and Trend Topics related to the keywords.